PANORAMIC OVERVIEW OF THE KEY FEATURES OF THE DEVELOPMENT AND PROBLEMATIC ASPECTS OF THE RUSSIAN GRAIN EXPORT-ORIENTED INDUSTRY IN MODERN CONDITIONS: DIGITAL GROWTH POINTS - E. A. Borshchova; V. S. Kokhanova (Вестник университета)
Тhe article reflects the most striking features of the development of the grain export-oriented industry of the Russian Federation. The authors highlight the main players, trends that have a significant impact on the pricing unit in the market and, as a result, the financial and economic condition of Russian exporters. The paper describes the current problems of the Russian grain market, demonstrates the real situation by the example of the functioning of one organization. The authors focus attention on a number of information and technological solutions that can neutralize the negative manifestations of the grain export segment, among them – on the grain movement control system, which is currently being developed on the instructions of the Government of the Russian Federation, in order to ensure openness and transparency of the agro-industrial complex.